Unique Aspects of Anti-cancer Drug Development (IntechOpen, 2023)
The evidence of cancer in humans, animals and plant species suggests that it is as old as multicellular life on Earth. Why is it so difficult to understand and fight? Because cancer begins from the organism's own mutated single cell focused on its own survival. It would be naive to expect that cancer could be ever entirely eliminated, but there is still hope for finding effective treatments. The book is to give a view of selected aspects of cancer like its spread in nature, novel anticancer drugs based on Chinese herbs or birch bark, novel promising targets of annexins and kinases and progress in immunotherapy. It is our hope that you will find in this book interesting, inspiring and stimulating information concerning cancer research.